Factors Related to Pain Intensity Post-SC with Spinal Anesthesia - Ni Luh Putu Lusiana Devi; I Ketut Setiabudi; Kadek Buja Harditya; Ni Nyoman Ari Kundari Dewi; Luh Gde Nita Sri Wahyuningsih (Indonesian Journal of Global Health Research, 2024)
Pain is the most common complaint found in perioperative patients, so optimal pain management is needed. Proper pain management can be done if the officer is able to know the intensity of pain felt by the patient and what factors are related. The aim of this study was to determine the pain intensity of post-CS patients with spinal anesthesia.This quantitative correlation study with a cross-sectional approach will be conducted involving 87 respondents based on the Slovin Formula. Sampling was carried out using purposive sampling to determine the selected sample. This study will use univariate data analysis techniques (frequency distribution and percentage), and bivariate data analysis (chi-square test). The results of the data analysis showed that the majority of patients had postoperative pain intensity on a scale of <2 as many as 52 people (60%). Age factors, gravida status, BMI, preoperative analgesics, and preoperative pain intensity have p-values> 0.05, namely 0.623, 0.137, 0.341, 0.570, 0.620. It can be concluded that there is no relationship between age, BMI, pre-operative pain intensity, and pre-operative analgesic administration with post-operative pain intensity in CS patients with spinal anesthesia.